Nursing team interventions in the coronavirus pandemic for intensive care unit patients: an integrative review (Research, Society and Development, 2022)
Objective: To know the main Nursing interventions for patients with COVID-19 in an intensive care unit. Methodology: This is a descriptive study of an integrative literature review, with searches in the LILACS, SCIELO AND MEDLINE databases in the last ten years. Results: After analyzing the titles of the articles and those that were related to the proposed theme, and the abstracts were read, guiding focuses were identified for the proposed objective of the research, with 7 articles selected for having corresponded to the theme of the bibliographic study, through the previously established inclusion and exclusion criteria. Conclusion: The Nursing team acts in an assistance way in the care of oxygen therapy, vital signs, cardiovascular, renal and neurological risk control, as well as in the control of the risk of spreading the pathogen, but in the face of the stress and fear generated by the pandemic, the ICU Nursing professionals suffer from psychological problems requiring care regarding their mental health.